FACTORS AFFECTING HIGHER EDUCATION STUDENTS’ INTEREST AND MOTIVATION IN CULTIVATING ENTREPRENEURSHIP - Nurhaliza Nurhaliza; Zuhrinal M. Nawawi (International Journal Labs, 2022)
This research aims to analyze the factors that influence interest and motivation in fostering an entrepreneurial spirit in students of the Faculty of Economics and Islamic Business of the State Islamic University of North Sumatra. This research uses qualitative approaches that are descriptive analysis of data collection techniques used are observation techniques, interviews. The research subjects amounted to 5 people with different majors consisting of students who have a business. The results of this study are factors that can affect entrepreneurship there are 4, namely opinion faktor, family environment, motivation, and community environment, but of these 4 factors that greatly affect the opinion factor.